(untitled) (Global Journal of Computer Science and Technology, 2012)
Our previous research paper 2018;A Focus on Testing Issues in Distributed Database Systems’ led us to a conclusion that Distributed Database Systems supports many good engineering practices but there is still place for refinements. A Distributed Database (DDB) is formed by a collection of multiple databases logically inter-related in a Computer Network. Apart from managing a plethora of complicated tasks, database management systems also need to be efficient in terms of concurrency, reliability, fault-tolerance and performance. As there has been a paradigm shift from centralized databases to Distributed databases, any testing process, when used in DDB correlates a series of stages for the construction of a DDB project right from the scratch and is employed in homogeneous systems. In this paper, an attempt is made to describe the establishment of Performance Testing with DDB systems. It focuses on the need for maintaining performance and some techniques to achieve performance in DDB systems. Three sample web based systems are tested by using TestMaker, one of the open source software, in order to highlight the helpful role of performance in the context of testing. The strengths and weaknesses of chosen performance testing tools viz., TestMaker, OpenSTA, and httperf are discussed.